Physical and environmental drivers of Paleozoic tetrapod dispersal across Pangaea - Neil Brocklehurst (Nature Portfolio, 2018)
The late Paleozoic was a time of major transition for tetrapods. Here, Brocklehurst and colleagues analyse the biogeography of Paleozoic tetrapods and find shifts in dispersal and vicariance associated with Carboniferous mountain formation and end-Guadalupian climate variability.